A Survey of Sensor Web Services for the Smart Grid - Omar Asad; Melike Erol-Kantarci; Hussein T. Mouftah (Journal of Sensor and Actuator Networks, 2013)
The broad use ofWireless Sensor Networks (WSN) in various fields have resulted in growing demand for advanced data collection and querying mechanisms embedded in the sensor node. Sensor Web Services (SWS) have recently emerged as a promising tool to enable external machines to have access to the information collected by public sensor webs. Machine-to-machine interactions or wireless sensor and actor networks can take advantage of this platform-independent technology to develop diverse smart grid applications. In this survey, we first briefly present the state of the art in SWS technology by describing the techniques for customizing web services to fit the sensor node capabilities such as customizing the WSDL file, compressing XML documents and redesigning TCP protocol. Then, we survey the studies that have utilized the SWS technology in smart grid applications. These studies have shown that SWS provide energy management capabilities to the consumers and the utilities, and they are well suited for smart grid integrated smart home solutions.